Pertumbuhan bank syariah pasca pandemi Covid-19 - Yatimi, Muh. Asrul (Maliki Interdisciplinary Journal, 2024)
The purpose of this writing is to investigate the growth of Sharia banks in Indonesia after the COVID-19 pandemic. The results of this research show that the development of Sharia banks has demonstrated sufficient existence during the COVID-19 pandemic. After the COVID-19 pandemic, the development of Sharia banks has grown very well and effectively. This is known from the analysis results, which show that the performance of Sharia banks in terms of CAR, ROA, BOPO, FDR, NPF, and KAP after COVID-19 is declared very healthy. In the development of Sharia banking assets, Sharia banking assets have experienced continuous growth from year to year, with Sharia bank assets in 2021 amounting to IDR 676.735 billion and continuing to rise to IDR 703.167 billion in 2022.